A Look at Orientalism and the Turkish Image in 15th and 19th Century Travel Books - BALCI, Aykut (International Journal of Contemporary Economics and Administrative Sciences, 2025)
In 15th and 19th century travelogues examining how the West perceived the East and how the image of Turks was shaped, Ottoman lands were generally depicted as a mystical, despotic, and exotic place. These travels are filled with narratives that reinforce Western prejudices, portraying Turks as cruel, barbaric, and despotic. The Turks and the Ottoman Empire have been both frightening and intriguing figures for the West. This negative perception has been reinforced, particularly by the Crusades and the Turks' proximity to Europe. Western views of the Turks have been influenced by cultural clashes and religious wars. The influence of the Turks in Europe has created a negative image over the years, and this perception continues today. Turkey's process of joining the European Union has been shaped by this historical perception and the image of the Turks. These writings have also reflected the imperialist perspective of the West, reinforcing the representation of the East as the “other.” The aim of this study, prepared using the qualitative research method of literature review, is to examine the historical origins of the Western world's negative perceptions of Turks and Islam and to show how these perceptions have persisted and developed to the present day.